2002
DOI: 10.1108/02656710210429618
|View full text |Cite
|
Sign up to set email alerts
|

ISO 9000 registration’s impact on sales and profitability

Abstract: Although there is a plethora of research articles that study ISO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(36 citation statements)
references
References 29 publications
2
28
0
6
Order By: Relevance
“…As is the case with the vast majority of quantitative studies, the information used in this paper is based on the perceptions given by specialized managers who had taken part in the EMS introduction process. Any analyses of the effect of EMSs conducted in this way are subject to possible weakness and methodological distortion, a bias problem that Wayhan and Balderson (2007), Wayhan et al (2002) and Heras et al (2002) have pointed out in the case of Quality Management, and Nawrocka and Parker (2009) have detailed in the case of CEM. With a view to avoiding this problem, the authors believe it would be interesting to analyze the benefits of EMSs or their influence in terms of environmental performance, based on objective environmental data.…”
Section: Discussionmentioning
confidence: 98%
“…As is the case with the vast majority of quantitative studies, the information used in this paper is based on the perceptions given by specialized managers who had taken part in the EMS introduction process. Any analyses of the effect of EMSs conducted in this way are subject to possible weakness and methodological distortion, a bias problem that Wayhan and Balderson (2007), Wayhan et al (2002) and Heras et al (2002) have pointed out in the case of Quality Management, and Nawrocka and Parker (2009) have detailed in the case of CEM. With a view to avoiding this problem, the authors believe it would be interesting to analyze the benefits of EMSs or their influence in terms of environmental performance, based on objective environmental data.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in the case of the ISO 9000 standard, many studies have emphasized the benefits of the standard in terms of improved quality, customer satisfaction and production management (Bhuiyan and Alam, 2005;Naveh and Marcus, 2005;Standards Council of Canada, 2000). On the other hand other studies, fewer in number, have questioned these benefits and consider that the standard has little or no impact on the improvement of performance (Acharya and Ray, 2000;Boiral, 2003;Heras et al, 2002;Wilson et al, 2003). The same kind of debate is repeated in the evaluation of the impacts of the ISO 14001 standard on improvements in environmental performance.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies, however, do not report these positive effects, at least not in all cases or circumstances (Heras et al 2002;Wilson et al 2003;Martínez-Costa and Martí-nez-Lorente 2007;Martínez-Costa et al 2009;Boiral and Amara 2009;Delic et al 2014). These studies have consistently shown that it is not enough to formally implement ISO 9001 simply to follow the trend or boost the firm's image.…”
Section: Positive Effects Of Implementing the Iso 9001mentioning
confidence: 99%